A pioneer of urologic surgery from a small town in Ontario, Canada: A tribute to Abraham Groves (1847-1935) - Caumartin, Yves; McAlister, Vivian C.; Luke, Patrick P.W. (Canadian Urological Association Journal, 2013)
Background: Abraham Groves worked as a general practitioner and surgeon in the small town of Fergus, Ontario, Canada. Several priority claims have been attributed to Groves’ life in surgery, including aseptic surgery (1874), appendectomy (1883) and the use of surgical gloves (1885). He was also an early practitioner of urological surgery. Objective: The purpose of this paper is to describe and objectively assess his contributions as a pioneer in urological surgery. Methods: A systematic search of contemporary journals was made for articles by or about Groves. These articles and his 1934 autobiography were reviewed. The information was assessed not only for priority, but also for the development of organized surgical principles and thought. Results: Groves published frequently throughout his career; up to this point, 36 papers have been identified. Groves’ claims are verifiable for aseptic surgery, which were the result of logical surgical thought and was practiced throughout his career. Contemporary publications support his early use of suprapubic lithotomy (1875), prostatotomy (1887), bladder repair (1892), urethral repair (1903), renal decapsulation (1905) and prostatectomy (1911). Conclusions: Despite his isolation, Abraham Groves independently developed a full range of surgical techniques and principles relevant to modern-day urology. His impact was reduced by the nature of the environment in which he worked and by the limited circulation of the journals in which he chose to publish. Contexte : Abraham Groves était omnipraticien et chirurgien dans la petite ville de Fergus, en Ontario. Plusieurs percées importantes lui ont été attribuées, comme la chirurgie en asepsie (1874), l’appendicectomie (1883) et l’emploi de gants chirurgicaux (1885). Il a aussi été un pionnier de la chirurgie urologique. Objectif : Le présent article vise à décrire et évaluer de façon objective les contributions d’Abraham Groves dans l’évolution de la chirurgie urologique. Méthodologie : Une recherche systématique des revues médicales de l’époque a permis de dégager des articles signés par Groves ou portant sur ses travaux. On a ensuite passé en revue ces articles et son autobiographie, datant de 1934. On cherchait dans ces documents non seulement des preuves de ses percées sur le plan scientifique mais aussi l’élaboration de principes et théories structurés en chirurgie. Résultats : Groves a publié de nombreux articles; jusqu’à présent, nous en avons trouvé 36. Il a été possible de confirmer les découvertes de Groves concernant la chirurgie en asepsie, technique découlant de la logique scientifique et qu’il a pratiquée durant toute sa carrière. Des articles de l’époque confirment son utilisation de la lithotomie sus-pubienne (1875), de la prostatotomie (1887), de la réparation vésicale (1892), de la réparation urétrale (1903), de la décapsulation rénale (1905) et de la prostatectomie (1911). Conclusions : En dépit de son isolement, Abraham Groves a élaboré de façon indépendante une gamme de techniques chirurgicales et de principes toujours pertinents en urologie de nos jours. Son influence a été limitée par la nature de son environnement professionnel et par la circulation limitée des périodiques dans lesquels il a choisi de publier.